Arsenic speciation and bioaccessibility in raw and cooked seafood: Influence of seafood species and gut microbiota. (1st July 2021) - Fu, Yaqi; Yin, Naiyi; Cai, Xiaolin; Du, Huili; Wang, Pengfei; Sultana, Mst Sharmin; Sun, Guoxin; Cui, Yanshan
Abstract: Seafood is an important source of arsenic (As) exposure for humans. In this study, 34 seafood samples (fishes, shellfishes, and seaweeds) collected from different markets in China were analysed for total and speciated As before and after boiling. Furthermore, the As bioaccessibility was also assessed using a physiologically based extraction test combined with the Simulator of Human Intestinal Microbial Ecosystems. The results showed that the total As (tAs) contents of seaweeds (raw: 44.12; boiled: 31.13, μg·g −1 dw) were higher than those of shellfishes (raw: 8.34; boiled: 5.14, μg·g −1 dw) and fishes (raw: 6.01; boiled: 3.25, μg·g −1 dw). Boiling significantly decreased the As content by 22.24% for seaweeds, 32.27% for shellfishes, and 41.42% in fishes, respectively ( p  < 0.05). During in vitro digestion, the bioaccessibility of tAs and arsenobetaine (AsB) significantly varied between the investigated species of seafood samples in gastric (G) and small intestinal phases (I) ( p  < 0.05). Higher tAs bioaccessibility (G: 68.6%, I: 81.9%) were obtained in fishes than shellfishes (G: 40.9%, I: 52.5%) and seaweeds (G: 31%, I: 53.6%). However, there was no significant differences in colonic phase (C) ( p  > 0.05). With the effect of gut microbiota, arsenate (As Ⅴ ) was transformed into monomethylarsonic acid (MMA) and arsenite (As Ⅲ ) in C. Moreover, as for seaweeds, an unknown As compound was produced. Graphical abstract: Image 1 Highlights: Seaweeds especially Hizikia fusiforme have high total arsenic (tAs) and inorganic As (iAs). Boiling decrease total arsenic concentration by 22.2–41.4% significantly. Arsenic released mostly in gastrointestinal phase for fishes, but in colonic phase for shellfishes and seaweeds. Arsenate (As Ⅴ ) was transformed into monomethylarsonic acid (MMA), arsenite (As Ⅲ ) under the effect of gut microbiota. As for seaweeds, an unknown component produced in the colonic phase.